Sağlık Hizmetlerini Yönetmek Neden Zordur?: Teorik Tartışmalar - Çakmak Barsbay, Mehtap (Muş Alparslan Üniversitesi, 2019)
Public health service organizations have distinctive and unique characteristics.They require a wide range of resources, from healthcare workers with professionalbackground and medical technology, to the basic consumables, and roboticmedical devices. Continued high labor intensity and capital-intensivetechnology are specific to healthcare services. Moreover, interdisciplinaryteam work is increasingly prevalent, and there has been a great deal ofchallenge supported by organizational and professional boundaries.  The aim of this study is to summarize thetheoretical and current discussions concerning management of health careorganizations different from general management perspectives of the othersectors.

Kamudasağlık hizmeti sunan kuruluşlar, diğer kamu kuruluşlarından farklı olarakkendine münhasır, spesifik özelliklere sahiptir. Sağlık hizmeti sunan kuruluşlar, hizmeti sunabilmek için farklı mesleklerden uzmanların işgücüne ve tıpteknolojisine, basit sarf malzemeden robotik özellikli tıbbi cihazlara kadargeniş perspektifte maddi kaynağa ihtiyaç duyarlar. Yoğun emek ve yüksekteknoloji kullanılan sağlık kurumları, karmaşık bir yapıya sahip olma ileberaber farklı mesleklerden sağlık çalışanlarının ekip halinde, disiplinlerarası uyum içinde çalışmalarının sağlanmasının önünde profesyonel veorganizasyonel zorlukların bulunduğu örgütlerdir. Bu çalışmada, sağlıkkurumlarını yönetmenin diğer sektörlere özgü yönetim anlayışından hangiperspektiflerde ayrıldığı konusunda teorik ve güncel tartışmalarözetlenmektir.
Why Is It So Hard to Manage Healthcare: Theoretical Discussions
anemon
Keywords: Health Services; Healthcare Organizations; Health Administration; Sağlık Hizmeti; Sağlık Kurumları; Sağlık Yönetimi